2019
DOI: 10.1103/physrevd.100.104045
|View full text |Cite
|
Sign up to set email alerts
|

Higher order corrections to deflection angle of massive particles and light rays in plasma media for stationary spacetimes using the Gauss-Bonnet theorem

Abstract: The purpose of this article is twofold. First, we extend the results presented in [1] to stationary spacetimes. Specifically, we show that the Gauss-Bonnet theorem can be applied to describe the deflection angle of light rays in plasma media in stationary spacetimes. Second, by using a correspondence between the motion of light rays in a cold non magnetized plasma and relativistic test massive particles we show that this technique is not only powerful to obtain the leading order behavior of the deflection angl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 51 publications
(84 reference statements)
1
45
0
Order By: Relevance
“…which matches well with the result of the Schwarzschild deflection angle of massive particles up to the second order via other approaches [58][59][60][61][62][64][65][66][67][68][69][70][71]. In the limit v 0 → 1, Eq.…”
Section: Gravitational Deflection Of Massive Particles Due To a Sds Black Holesupporting
confidence: 87%
“…which matches well with the result of the Schwarzschild deflection angle of massive particles up to the second order via other approaches [58][59][60][61][62][64][65][66][67][68][69][70][71]. In the limit v 0 → 1, Eq.…”
Section: Gravitational Deflection Of Massive Particles Due To a Sds Black Holesupporting
confidence: 87%
“…Let us now turn our attention to the gravitational deflection of relativistic massive particles in the spacetime of a LQBH using the approach introduced in Ref. [107]. It is worthwhile to mention that the calculation of the deflection angle for different black holes is a very attractive area in the studying of strong gravity features of black holes, see refs.…”
Section: Gravitational Deflection Of Massive Particlesmentioning
confidence: 99%
“…Note that l is an affine parameter [107], and S and R represent the source and receiver, respectively. Calculating the Gaussian optical curvature to leading order terms we find…”
Section: Gravitational Deflection Of Massive Particlesmentioning
confidence: 99%
“…Jia in [32] scrutinizes the weak gravitational deflection of relativistic massive particles for a receiver and source at finite distance from the lens in stationary, axisymmetric and asymptotically flat spacetimes by extending the generalized optical metric method to the generalized Jacobi metric method using the Jacobi-Maupertuis Randers-Finsler metric. Crisnejo et al have shown that the Gauss-Bonnet theorem can be applied to describe the deflection angle of light rays in plasma media in stationary spacetimes in [33] and also have obtained the leading order behavior of the deflection angle of massive/massless particles in the weak field regime with higher order corrections in a cold non magnetized plasma. The equivalence of the Gibbons-Werner method to the standard geodesic method with the case study of Kerr-Newman spacetime especially for the asymptotically flat case in [34] by Li and Zhou.…”
Section: Introductionmentioning
confidence: 99%